The Effect of Liquidity on the Performance of Foreign Banks in Indonesia - Muhammad Akbar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to examine the effect of liquidity on bank performance. In this study, a quantitative method approach was used to achieve the objectives and answer research questions and test the hypotheses that had been developed. This study also uses dynamic panel data analysis based on the panel data model framework.The type of data used is secondary data, namely data/information on foreign banks listed on the IDX for the 2010-2016 period, sourced from the IDX, BI, and OJK. Meanwhile, the data collected is liquidity and bank performance. The unit of analysis is limited to foreign banks registered with the Financial Services Authority (OJK). The population in this study are foreign banks listed in the Financial Services Authority (OJK) for the 2010-2016 period, as many as 10 banks (cross-section), where the periodization of financial statements is determined for 7 years, namely 2010-2016 (time series), including for meet the data analysis requirements and to represent the population taken. Foreign bank performance is measured by ROA (Return on Assets), ROE (Return on Equity), CAR (Capital Adequacy Ratio), NPL (Non-Performing Loan). The results showed that there was no significant effect of Liquidity on ROA; there is a significant effect of Liquidity on ROE; there is no significant effect of liquidity on CAR; there is a significant effect of liquidity on NPL. So liquidity only has a significant effect on ROE and NPL.